Efficient Multi-WAN Transport for 5G with OTTER - Hogan, Mary; Wan, Gerry; Qiu, Yiming; Agarwal, Sharad; Beckett, Ryan; Singh, Rachee; Bahl, Victor (USENIX NSDI, 2025)
In the ongoing cloudiﬁcation of 5G, software network functions (NFs) are replacing ﬁxed-function network hardware, allowing 5G network operators to leverage the beneﬁts of cloud computing. The migration of NFs and their management to the cloud causes 5G trafﬁc to traverse an operator’s wide-area network (WAN) to the cloud WAN that hosts the datacenters (DCs) running 5G NFs and applications. However, achieving end-to-end (E2E) performance for 5G trafﬁc across two WANs is hard. Placing 5G ﬂows across two WANs with different performance and reliability characteristics, edge and DC resource constraints, and interference from other ﬂows is different and more challenging than single-WAN trafﬁc engineering. We address this challenge and show that orchestrating E2E paths across a multi-WAN overlay allows us to achieve average 13% more throughput, 15% less RTT, 45% less jitter, or reduce average loss from 0.06% to under 0.001%. We implement our multi-WAN 5G ﬂow placement in a scalable optimization prototype that allocates 26%–45% more bytes on the network than greedy baselines while also satisfying the service demands of more ﬂows.